Three years of trace gas observations over the EuroSiberian domain derived from aircraft sampling - a concerted action - Levin, Ingeborg; Schmidt, Martina (Universitätsbibliothek der Universität Heidelberg, 2002)
A three-years trace gas climatology of CO2 and its stable isotopic ratios as well as CH4, N2O and SF6, derived from regular vertical aircraft sampling over the Eurasian continent is presented. The four sampling sites range from about 1°E to 89°E in the latitude belt of 48°N to 62°N. The most prominent features of the CO2 observations are an increase of the seasonal cycle amplitudes of CO2 and delta13C-CO2 in the free troposphere (at 3000 m a.s.l.) by more than 60% from Western Europe to Western and Central Siberia. delta18O-CO2 shows an even larger increase of the seasonal cycle amplitude by a factor of two from Western Europe towards the Ural mountains, which is decreasing again towards the most eastern site Zotino. These data reflect a strong influence of carbon exchange fluxes with the continental biosphere. In particular, during autumn and winter 18O-CO2 shows a decrease by more than 0.5 from Orléans (Western Europe) to Syktyvkar (Ural mountains) and Zotino (West Siberia), mainly caused by soil respiration fluxes depleted indelta18O with respect to atmospheric CO2. CH4 mixing ratios in the free troposphere at 3000 m over Western Siberia are higher by about 20-30 ppb if compared to Western Europe. Wetland emissions seem to be particularly visible in July-September with largest signals at Zotino in 1998. Annual mean CH4 mixing ratios slightly decrease from 1998 to 1999 at all Russian sites. In contrast to CO2 and CH4 which show significant vertical gradients between 2000 and 3000 m a.s.l., N2O mixing ratios are vertically very homogeneous and show no significant logitudinal gradient between Ural mountains and Western Siberia, indicating insignificant emissions of this trace gas from boreal forest ecosystems in Western Siberia. The growth rate of N2O (1.2 to 1.3 ppb/yr) and the seasonal amplitude (0.5 to 1.1 ppb) are similar at both aircraft sites, Syktyvkar and Zotino. For SF6, an annual increase of 5% is observed, and a small seasonal cycle which is in phase with the N2O cycle, indicating that the seasonality of both trace gases are most probably caused by atmospheric transport processes with a possible contribution from stratosphere-troposphere exchange.
Aus: Tellus 54B, Seiten 696-712